Gamification Framework for Early Childhood Flood Disaster Preparedness in Indonesia: A Systematic Literature Review - Mallevi Agustin Ningrum; Fauziddin, Mohammad; Zainal Abidin, Mohd. Syahidan (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2026)
Indonesia’s repeated exposure to hydrometeorological hazards, particularly floods, makes disaster preparedness a pressing educational concern from the early years of life. Yet research on disaster learning for young children remains limited, and gamification has rarely been examined in this area with sufficient conceptual precision. This study addresses that gap through a systematic literature review guided by PRISMA 2020, focusing on how gamified approaches have been used in flood-related disaster education for early childhood contexts. Searches of Scopus, Web of Science, ScienceDirect, Wiley Online Library, and DOAJ covered publications from 2015 to 2025. Of 340 records identified, 28 studies met the inclusion criteria and were synthesised through thematic analysis and narrative synthesis. Three recurrent patterns emerged. Gamification was most educationally meaningful when it functioned as pedagogical scaffolding rather than as a reward system, enabling children to approach abstract risk through staged, participatory learning. Play-based simulation, feedback, and repetition also appeared to create psychologically safer ways of engaging difficult topics. Its value, however, was strongly shaped by context, especially in settings marked by uneven infrastructure, limited pedagogical resources, and high disaster exposure. The review therefore does not support broad claims that digital enhancement is inherently effective in disaster education. Instead, it suggests that gamification matters when it is developmentally grounded and carefully aligned with early childhood pedagogy. The study contributes to international discussion by recasting gamification less as a motivational device than as a form of pedagogical mediation in early childhood disaster education, particularly in settings where vulnerability is high and educational conditions are uneven. It also points to the need for further work across a wider range of hazards, settings, and pedagogical designs.